Behavior of Rectangular Footing Subjected to Gypseous Soil under Two way Eccentricity - Vertical Load - Adnan Jayed Zedan; Mohammed Chyad Liejy Ali AL-Hadeddy (Kirkuk Journal of Science, 2017)
In this study the behavior of rectangular footing on gypsum soil is studied under vertical eccentric loads through two way ( x–y) via fabrication of a simulator of (100 mm * 150 mm) for the rectangle footing. By using the (Bubble ) program in the mobile for measurement tilt of footing by putting it on the foundation , fabrication of load tester and putting the soil in a box having a dimensions of (900 mm * 900 mm) and depth( 600 mm). A sample of soil is taken from the Tikrit University in Salah Al Din government under (0.5- 3 ) m depth which has a gypsum content of (51.37 %) using (Al-Mufty and Nashat 2000) method. The load test is performed on square and rectangle footing at eccentricity of through two way ( x–y) (e/B= 0, 0.1, 0.2, 0.3) The local specifications of the soil are measured (density, moisture, maximum density and optimum moisture content), it is found that that the vertical settlement, in two sides increases with the increasing of eccentricity and of the load, the bearing capacity is nearest to the theoretical results for (Meyerhof Eq. 1953) and less than the (Hansen Eq., 1970) in vertical load in site density and moisture .It is also observed that bearing capacity decreases with the increasing of eccentricity of the load because small area of effectual foundation . at site density and moisture , whereas it approaches the theoretical results to the (Meyerhof Eq., 1953 ) and theoretical result was less than of ( Hanson eq., 1970) when the vertical load . :